Investigation on the Wear Behavior of Spray Formed Al–35Si–4Fe Alloy - Goudar D.M.; Raju K.; Ojha S.N. (My University, 2025)
In the present study the microstructural features, hardness and wear properties of spray formed Al–35Si–4Fe alloy have been compared with that of as-cast alloy. The microstructure of spray formed Al–35Si–4Fe alloy consisted of fine and uniformly distributed Si coexisting with granular Fe containing intermetallic phase in Al matrix. In contrast, the microstructure of as-cast alloy consisted of coarse Si plates and needles of β-Al–Fe–Si phase in Al matrix. The hardness of spray formed alloy was found to be higher than that of as-cast alloy. The dry sliding wear tests at varying load and sliding speed revealed that wear rate and coefficient of friction for spray formed alloy were invariably lower than that of as-cast alloy. The high hardness and wear resistance of spray formed alloy were discussed in the light of its microstructural features and the morphology of worn-out surfaces. © 2015, The Indian Institute of Metals - IIM.